Aktualisasi Manajemen Organisasi pada Timang News dalam Mempertahankan Eksistensi dan Konsistensi - Agus Salim; Al Zuhri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
UKM Timang News in 2023 is stagnant in all its lines. From the results of initial observations, it was found that management was not working well, so this became the author's attention, highlighting the real root of the problem. To achieve this goal, the author uses Terry's POAC theory with descriptive qualitative methods. The results showed that the management of UKM Timang News for the 2021-2022 period was still not optimal, which also had an impact on Timang News’ inability to maintain its existence and consistency. This can be seen from the lack of comprehensive organizational management. At the planning stage, Timang News has implemented it very well by arranging careful planning such as determining the time and number of news publications each week. Likewise, at the organizing stage, Timang has arranged and divided the fields, members and tasks of each member well. However, big obstacles were encountered when the program entered the actuating and controlling stages, all activities became stagnant and irregular. After conducting research, it was found that the factors were that many administrators were busy with their respective end-of-course activities, members did not have strong work motivation because members were recruited through appointment rather than selection, lack of loyalty and responsibility, and others. UKM Timang News should be useful in its existence in the campus environment in encouraging students' intellectual and critical thinking so it would be a shame if its existence could not continue.